(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Considering that the vibratory forces generally cannot be measured directly at the interface of two bodies, an inverse method is studied in the present work to recover the loadÂ history in such cases. The proposed technique attempts to reconstruct the dynamic loadsÂ history by using a frequency domain analysis and Moore-Penrose pseudo-inverses of theÂ frequency response function (FRF) of the system. The methodology consists in applyingÂ discrete dynamic loads on a finite element model in the time domain and retrieve estimates ofÂ the loads at points that cannot be measured, and complementing these data with theÂ experimental results. Since the number of points of interest in general differs from the numberÂ of points experimentally tested, the FRF matrix results rectangular, then the need of pseudoinverses. Additionally, a regularization procedure is used to smooth the reconstructed load history, aiming the removal of spurious peaks. A case is illustrated to describe the method. Keywords: Load Reconstruction, Pseudo-Inverse, Moore-Penrose Pseudo-Inverse, Structural Dynamics, Load History.